Edukasi Manajemen Koping Pada Remaja Terhadap Problematika Kehidupan Sehari-Hari - wijaya, endah; Dhian Ika Prihananto; Siti Aizah; Ratih Ayu Kinasih; Cyndi Fitriana Nursita; Sapto Widy Wijayanto (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Adolescence is a phase of physical, cognitive, psychosocial, and emotional transition. This phase allows adolescents to experience with problems and stress. Problems and stress can be managed by self-coping management. This activity aims to determine students' stress levels and increase their understanding of coping management. The activity was carried out on November 29, 2022 at SMK PGRI 3, Kediri with 31 participans. Activities carried out by the method of lectures, discussions, and games. Activity evaluation is comparing pre and post test scores. The results showed that there was an increase in knowledge of 13% after being given counseling. This education must be carried out continuously so that students are truly able to understand and do it in everyday life. The school is expected to create a program to monitor student stress levels as well as an educational program on self-coping management.